Reducing Gun Violence in America Informing Policy with Evidence and Analysis - Vernick, Jon S.; Webster, Daniel W. (Johns Hopkins University Press, 2013)
Outstanding Academic Title, Choice MagazineThe staggering toll of gun violence-which claims 31,000 U.S. lives each year-is an urgent public health issue that demands an effective evidence-based policy response.The Johns Hopkins University convened more than 20 of the world's leading experts on gun violence and policy to summarize relevant research and recommend policies that are both constitutional and have broad public support. Collected for the first time in one volume, this reliable, empirical research and legal analysis will help lawmakers, opinion leaders, and concerned citizens identify policy changes to address mass shootings, along with the less-publicized gun violence that takes an average of 80 lives every day.Selected recommendations include:• Background checks: Establish a universal background check system for all persons purchasing a firearm from any seller. • High-risk individuals: Expand the set of conditions that disqualify an individual from legally purchasing a firearm. • Mental health: Focus federal restrictions on gun purchases by persons with serious mental illness on the dangerousness of the individual.• Trafficking and dealer licensing: Appoint a permanent director to ATF and provide the agency with the authority to develop a range of sanctions for gun dealers who violate gun sales or other laws. • Personalized guns: Provide financial incentives to states to mandate childproof or personalized guns. • Assault weapons and high-capacity magazines: Ban the future sale of assault weapons and the future sale and possession of large-capacity ammunition magazines.• Research funds: Provide adequate federal funds to the Centers for Disease Control and Prevention, National Institutes of Health, and National Institute of Justice for research into the causes and solutions of gun violence.The book includes an analysis of the constitutionality of many recommended policies and data from a national public opinion poll that reflects support among the majority of Americans-including gun owners-for stronger gun policies. Amid a growing consensus that the staggering toll of gun violence in the United States is an urgent public health issue, the Johns Hopkins University's Bloomberg School of Public Health has convened experts on gun policy and violence from the United States and selected other countries to summarize relevant research and its implications for policymakers and concerned citizens. Legal scholars weigh in on the constitutionality of recommended policies, and researchers present new data on public support for a wide array of policies designed to reduce gun violence. Collected for the first time in one volume, this reliable, empirical research and legal analysis will inform the policy debate by helping lawmakers and opinion leaders identify the policy changes that are most likely to reduce gun violence in the United States.Researchers draw on new and existing studies on U.S. gun policies to demonstrate both the weaknesses of current federal gun policies and the efficacy of various state laws designed to reduce firearm availability to high-risk groups. By analyzing scientific and legal data, the contributors provide evidence in support of enhanced regulation and oversight of licensed gun dealers, background checks for private sales, and purchaser licensing. Lessons from bans of assault weapons and of large-capacity magazines for guns are considered, as is the promise of "smart guns," which could be fired only by authorized users. Compelling case studies from Australia, Scotland, and Brazil demonstrate effective policy responses to gun violence that have led to significant reductions in gun-related deaths. The book concludes with data on public support for strengthening gun laws and Second Amendment considerations.